Preparation of SilicaSilica Core-Shell Microspheres Using an Aqueous Two-Phase System in a Novel Microchannel Device - Li, Jie (Langmuir : the ACS journal of surfaces and colloids, 2020)
In the present work, a novel microchannel device was developed and used for the preparation of core-shell microspheres combining with a dextran/poly(ethylene glycol) diacrylate (DEX/PEGDA) aqueous two-phase system. Silicasilica core-shell microspheres were prepared as a model material. Silica@silica core-shell microspheres with different sizes of cores and thicknesses of shells were prepared by using different flowrate ratios of DEX/silica and PEGDA/silica aqueous solutions. The content of colloidal silica and the calcination temperature have a significant effect on the texture properties of the prepared core-shell microspheres. The surface area decreased from 199 to 177 m2/g with an increase in the colloidal silica content from 30 to 60 wt %. For a specific colloidal silica content (50 wt %), with the increase in calcination temperature from room temperature to 650 °C, the total pore volume went through a maximum of 0.7 cm3 g-1 with a surface area of 178 m2 g-1 and pore size of 7.32 nm at 450 °C. Due to the accumulation of metal nanoparticles in DEX, different metal nanoparticles (Ni and Pd) were successfully introduced into the core of the core-shell microspheres for the preparation of silica/metal nanoparticles@silica core-shell microsphere catalysts. The catalysts showed similar catalytic performance as the metal nanoparticles for hydrogenation of 4-nitrophenol with a conversion higher than 95%. However, the core-shell microsphere catalyst is much easier to recover. The reuse experiments indicated that the core-shell catalyst has high stability